2007
DOI: 10.1111/j.1365-2567.2007.02564.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis heat‐shock protein 70 impairs maturation of dendritic cells from bone marrow precursors, induces interleukin‐10 production and inhibits T‐cell proliferation in vitro

Abstract: Summary In different inflammatory disease models, heat‐shock proteins (hsp) and hsp‐derived peptides have been demonstrated to possess anti‐inflammatory properties. While some studies have shown that hsp can directly interact with antigen‐presenting cells, others report that bacterial hsp can induce specific T cells with regulatory phenotypes. Effective characterization of the immunomodulatory effects of hsp 70, however, has historically been confounded by lipopolysaccharide (LPS) contamination. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 66 publications
5
66
0
Order By: Relevance
“…Consequently, we believe that our straightforward experimental setup provided true representation of Hsp70 function. In addition, our results are in agreement with the study by Motta et al where the PHA-induced proliferative response of murine splenocytes was down-regulated by endotoxin-free Mycobacterium tuberculosis Hsp70 (15).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consequently, we believe that our straightforward experimental setup provided true representation of Hsp70 function. In addition, our results are in agreement with the study by Motta et al where the PHA-induced proliferative response of murine splenocytes was down-regulated by endotoxin-free Mycobacterium tuberculosis Hsp70 (15).…”
Section: Discussionsupporting
confidence: 83%
“…The shared activation pathway as well as the similar activation profile for endotoxins and Hsp70 led to speculation that the observed cytokine-like property of Hsp70 may have been incorrectly identified. Accordingly, it was shown that the endotoxin contamination in recombinant Hsp70 is common and exclusively responsible for the described proinflammatory properties, including activation of APCs (12)(13)(14)(15)(16). It was also shown that endotoxin-free Hsp70 did not induce APC activation while still effectively delivered antigenic peptides for cross-presentation (17).…”
Section: Strongly Suggest That Hsp70 Might Dampen Rather Than Provokmentioning
confidence: 99%
“…Heat shock proteins are also known for their immunomodulator properties. In Mycobacterium tuberculosis, DnaK was reported for its immunosuppressive properties (22), which also suggests a new potential of our mutant strains for health-promoting applications.…”
Section: Discussionmentioning
confidence: 99%
“…Hsp70 induces the expression of IL-10 and inhibits T-cell proliferation in vitro. Hsp70 appears to have immunosuppressive properties rather than inflammatory potential (Motta et al, 2007).…”
Section: Hsps As Antigens In M Tuberculosismentioning
confidence: 99%